Histostructure of pancreas in patients with autoimmune pancreatitis type I and II: connection with the level of IgG4-positive plasma cells - Y. A. Gaidar; N. Y. Oshmyanska; A. P. Halenko (Zaporozhye State Medical University, 2014)
Differential diagnosis of autoimmune pancreatitis apart from everything else is based on specifi cs of immunoglobulin G4 involvement into the pathogenesis. Aims: to analyze two forms of autoimmune pancreatitis and their relation to the level of IgG4-positive plasma cells. Methods and results. The present study was conducted on 54 patients with chronic pancreatitis, from which 15 cases with autoimmune pancreatitis were selected by using morphological and immunohistochemical methods. Conclusion. It has been established that for autoimmune pancreatitis type I dense lymphocytic periductal infi ltrate, multilevel fi brosis, obliterating venulitis and high IgG4-positive plasma cells in the pancreas (≥ 30 per high power fi eld) were typical. In the cases of autoimmune pancreatitis type II, besides the specifi c histopathological signs of AIP, signifi cantly epithelial damage of pancreatic ducts by leukocytes, low levels of IgG4-PPC in the pancreas and focal lesions on stages I-III of disease (80%) were observed.